SPECIFIC ASPECTS OF ENSURING THE ECONOMIC SECURITY OF INDUSTRIAL ENTERPRISES IN THE DEVELOPMENT OF THE DIGITAL ECONOMY - Uktamov Khusniddin Fakhriddinovich (Scholar Express Journals, 2023)
The progressive development of regions as open multi-level systems in the context of aggravating contradictions between the interests of economic agents at the stages of deteriorating macroeconomic conditions and intensifying competition at the global and national levels determine the need to form an effective system of economic security at the meso-level, taking into account numerous threats and risk-forming factors. On the one hand, the digital transformation of enterprises provides competitive advantages in the market, on the other hand, it is a challenge that threatens the very existence of the enterprise.
Keywords: industrial enterprises; economic security; economic security of enterprises; indicators of assessment